(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
A number of the world’s population is getting increased year by year. This leads to the increase in the number of cities and expansion of the existing ones. Today there are different views on cities: “Mega cities”, “Eco cities” and “Smart cities” and some others. This article provides information about “Smart cities”.